Self-rated health does not explain the socioeconomic differential in mortality: a prospective study in the EPIC-Norfolk cohort. Issue 4 (15th January 2009) - McFadden, E; Luben, R; Bingham, S; Wareham, N; Kinmonth, A-L; Khaw, K-T
Abstract : Background: Self-rated health (SRH), a subjective measure of health, is strongly predictive of mortality, independently of objective measures of health status and existing known disease. There is a strong social gradient in SRH. An investigation was carried to determine whether SRH can explain the well-known socioeconomic gradient in mortality. Methods: The effect of adjusting for SRH on the socioeconomic differential in mortality was examined in a prospective study of 20 754 men and women aged 39–79 years, without prevalent disease, living in the general community in Norfolk, UK, recruited using general practice age–sex registers for 1993–1997 and followed up for an average of 10 years. Results: Mortality risk increased with decreasing social class in men and women. There was some attenuation after adjustment for covariates age, body mass index, smoking, history of diabetes, systolic blood pressure, cholesterol level, alcohol consumption, physical activity and educational level, but a gradient remained. Further adjustment for SRH attenuated the association slightly more, but there was still some evidence of a socioeconomic differential in mortality, particularly in class V compared with class I (age- and sex-adjusted hazard ratio 1.57; 95% CI 1.19 to 2.06). Conclusions: SRH does not substantially explain the socioeconomic differential in mortality beyond that explained by health-related covariates.